Fever and neck pain after pacemaker lead extraction: A case report - Wang, Shao-Xian (World J Clin Cases, 2019)
BACKGROUND: Venous thrombosis (VT) is one of the minor complications of pacemaker lead extraction. It is often found due to the swelling of the limbs after the extraction. It is easy to be neglected or even misdiagnosed in the absence of typical clinical symptoms. The incidence, risk factors, and long-term impact of this complication are still unclear. Herein, we report a case of deep VT caused by transvenous lead extraction, which is easily misdiagnosed. CASE SUMMARY: A 66-year-old woman underwent a pacemaker lead extraction at our hospital because of a pacemaker pocket infection. After the extraction, she began to experience intermittent fever accompanied by sweating. The highest body temperature recorded was 37.9 °C. Additionally, she reported migratory pain that made her uncomfortable. The pain was mistakenly thought to be caused by operation trauma. At first, the pain radiated from the left chest to the mandible. Then, the pain in the left chest was alleviated, but pain in the left neck and throat appeared. Finally, the pain was confined to the mandible and a submandibular mass was palpated with no other abnormalities upon physical examination. Computed tomography venography and angiography finally indicated that the fever and pain were the symptoms of thrombophlebitis caused by lead extraction. The patient was then treated with rivaroxaban for more than three months and has shown no symptoms since she left the hospital. CONCLUSION: The possibility of thrombosis should be considered when pain and recurrent fever occur after pacemaker lead extraction.